Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1002/nop2.1241
|View full text |Cite
|
Sign up to set email alerts
|

The mediating effects of social support on the influencing relationship between grit and academic burnout of the nursing students

Abstract: Aim(s) This study aimed to examine the social supports' mediating effects on the relationship between grit and academic burnout in nursing students. Design This was a descriptive study. Methods This study was conducted in two nursing departments in Korea, utilizing a convenience sample of 158 nursing students. Data were analysed using hierarchical multiple regression analysis and bootstrapping to verify the mediation effect. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…The existence of social support can also increase grit in professional students. This has an impact on improving academic performance and reducing academic burnout, as well as adequate information support and emotional support, which can also help students' mental health [24]. Students who have high self-efficacy and social support during the education period, tend to have stress levels that are not too high [25].…”
Section: Create a Discussionmentioning
confidence: 99%
“…The existence of social support can also increase grit in professional students. This has an impact on improving academic performance and reducing academic burnout, as well as adequate information support and emotional support, which can also help students' mental health [24]. Students who have high self-efficacy and social support during the education period, tend to have stress levels that are not too high [25].…”
Section: Create a Discussionmentioning
confidence: 99%
“…In this regard, Kim and Lee justified that students who are dissatisfied with their university life have high academic burnout. It appears that interest in the field of study is important in reducing academic burnout [ 22 ]. Abuddous et al showed negative and significant correlations between the dimensions of burnout and satisfaction.…”
Section: Discussionmentioning
confidence: 99%